Morbidity and Mortality in Late Preterm Newborns Followed in a Neonatal Intensive Care Unit - Fatma Cakmak Celik (Mashhad University of Medical Sciences, 2022)
Background: Neonates born between 340/7-366/7 gestational weeks are considered late preterms with fewer risks, compared to smaller babies and more risks for morbidity and mortality than their term peers. The present study aimed to analyze maternal problems, as well as morbidity and mortality of late preterms followed in the Neonatal Intensive Care Unit.Methods: A total of 230 neonates' files were analyzed, and demographic characteristics, respiratory, as well as metabolic  and maternal problems, were recorded in this study.Results: Out of 230 neonates, 166 (72, 2%) and 129 (56,1%)  newborns were inborn and male, respectively. Moreover, 23 (10%) neonates were born through vaginal delivery. The mean birth weight of the neonates was estimated at 2532.1±540.3 gr. In total, 66, 71, and 93 infants were 34 0/7 and 34 6/7, 35 0/7-356/7, as well as 36 0/7-36 6/7, respectively. The premature rupture of membranes, placenta previa, ablatio placenta were obtained at 9.1% (n=21), 2.2% (n=5), and 3.5% (n=8), respectively.In addition, preeclampsia (n=24; 10.4%), cholestasis of pregnancy (n=7; 3%), oligohydramnios (n=26; 11.3%), and gestational diabetes mellitus (n=27; 11.7%) were observed in this study. The rates of transient tachypnea of the newborn, respiratory distress syndrome, polycythemia, hypoglycemia, indirect hyperbilirubinemia with intensive phototherapy, and feeding intolerance was estimated at 72.2% (n=166), 7.8% (n=18), 5.6% (n=13), 6.1% (n=14), 4.3% (n=10), and 8.7% (n=20), respectively. Any maternal problems and cholestasis of pregnancy were significantly more likely in 340/7 and 346/7 gestational weeks, compared to others (for any maternal problem and cholestasis of pregnancy: P=0.009 and P=0.012, respectively).Conclusion: Evaluation of the late preterms as terms may lead to neglecting some problems. Therefore, late preterms should be closely monitored, especially for respiratory problems in terms of intensive care requirements.